Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Sepeda Motor Honda Matic di PT Astra Honda Motor Cabang Negara Kabupaten Jembrana - Tabita, I Dewa Ayu Tita Permata; I Gusti Agung Sasih Gayatri,; Ida Gede Aninditha Negarakertawijaya, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
In line with the public's need and demand for adequate transportation facilities, city streets are increasingly crowded and traffic is increasingly congested by motorized vehicles. Encouraging the development of the automotive industry in Indonesia more quickly and tends to increase every year. The market demand for motorized vehicles is faced by automotive motorbike manufacturers, one of which is PT Astra Honda Motor, Jembrana Regency State Branch. This research uses a quantitative approach with the results of the research showing that variables X1 (Price) and ≤ 5% (0.05).